Effect of pH and ionic strength on functional, structural, and interfacial rheological properties of aquafaba - Parlak, Mahmut Ekrem; Ozmen, Duygu; Toker, Omer Said; Inan, Mehmet; Sarıcaoğlu, Furkan Turker (Elsevier B.V., 2025)
This study explored the nuanced influence of pH and ionic strength on aquafaba and investigated its viability as a plant-based alternative in food formulation. Functional assessments, including foaming capacity (FC), foam stability (FS), emulsifying activity index (EAI), and emulsifying stability index (ESI), underscore the critical role of pH. FC and FS peaked at pH 4, whereas EAI was highest at pH 5, highlighting the significant impact of protein net charge on aquafaba functionality. However, although increasing the ionic strength decreased the absolute zeta potential, the foaming and emulsifying properties differed. Rheological analysis confirmed non-Newtonian shear-thinning behavior, which shifted toward Newtonian-like behavior near the isoelectric point. The increasing ionic strength significantly increased the ?-helix content by decreasing the ?-structure content, which increased the adsorption rate of aquafaba at the air/water (A/W) interface. The pH-dependent adsorption rates highlight the importance of the net surface charge of the adsorbed molecules. The interfacial shear rheology results showed that while the foaming properties of aquafaba are dominated by the adsorption rate, the emulsifying properties are mainly dominated by the interactions between adsorbed molecules rather than the adsorption rate at the oil/water (O/W) interface. In summary, this study provides comprehensive insights into the intricate interplay between pH and ionic strength in aquafaba, which is crucial for the formulation of sustainable plant-based alternatives in the food industry. © 2025 Elsevier B.V.
Keywords: Aquafaba; Functional properties; Interfacial rheology; Ionic strength; pH effect